The Impact of Gender on Postoperative Complications after Revision Total Knee Arthroplasty - Gu, Alex; Wei, Chapman; Bernstein, Simone A.; Nguyen, Nam Tran T.; Sobrio, Shane A.; Liu, Jiabin; Sculco, Peter K. (The Journal of Knee Surgery, 2020)
Knee osteoarthritis is a common form of arthritis, often treated by total knee arthroplasty (TKA). Complications can arise after TKAs, which may necessitate revision TKAs and further treatments. However, there remains a paucity of literature regarding influence of gender on postoperative complication rates after revision TKA. A retrospective cohort study was conducted using the American College of Surgeons National Surgical Quality Improvement Program database. Patients who received revision TKAs between 2007 and 2014 were identified and recorded as male or female. Univariate and multivariate analysis was used to evaluate the incidence of multiple adverse events within 30 days of revision TKA. This study included 9,914 patients who underwent revision TKA (females = 5,728 [57.8%]; males = 4 186 [42.2%]). Male patients were shown to be at greater risk for developing 7 of 17 complications compared with female patients, and female patients were shown to be at greater risk for urinary tract infection (UTI) development. Multivariate analysis showed males as an independent risk factor for four complications and females as an independent risk factor for UTI development. Male patients were more likely to develop more complications postoperatively than female patients. Although the possibility of developing complications is relatively low, orthopaedic surgeons should be aware of increased postoperative complication rates when counseling patients who undergo revision TKA.
Keywords: revision; knee; arthroplasty; gender; male; female